Accessing Enantiopure Epoxides and Sulfoxides: Related Flavin‐Dependent Monooxygenases Provide Reversed Enantioselectivity. Issue 1 (23rd October 2019) - Heine, Thomas; Scholtissek, Anika; Hofmann, Sarah; Koch, Rainhard; Tischler, Dirk
Abstract: Enantiopure organic compounds are of major importance for the chemical and pharmaceutical industry. Flavin‐dependent group E monooxygenases, composed of monooxygenase and reductase, are known to perform epoxidation of substituted alkenes as well as sulfoxidation in a regio‐ and enantioselective fashion. Group E is divided into styrene monooxygenases (SMO) and indole monooxygenases (IMO). Hitherto mainly SMOs have been characterized. In this study, we assayed 31 monooxygenases from both types, while 23 of which showed activity. They almost exclusively produced ( S )‐styrene oxide at high enantiomeric excess with maximum activities of 0.73 μmol min −1 mg −1 ( k cat =0.54 s −1 ). In case of sulfoxidation, we found that the enantioselectivity is contrary between both types. IMOs preferably produce the ( S )‐enantiomer while SMOs have a tendency to produce the ( R )‐enantiomer. Sequence analysis and molecular docking of substrates allowed identifying fingerprint motives: SMO N46‐V48‐H50‐Y73‐H76‐S96 and IMO S46‐Q48‐M50‐V/I73‐I76‐A96 . These form an essential part of the active site while the loop (AS44‐51) interacts with the co‐substrate and other amino acids direct the substrate. The motives clearly distinguish group E monooxygenases and define the enantioselectivity and thus direct biotechnological applications. Two‐hour biotransformations with several sulfides in conjunction with upscale experiments (10 and 100 mg scale) resulted in the identification of promising candidates for the realization of biocatalytic processes. Abstract : The tree of GEMs : The "fruits" of Group E Monooxygenases are epoxides and sulfoxides. By characterization of various representatives, it was possible to show that the enantioselectivity is dependent on the phylogenetic subgroup. An expanded scope of GEM allows taking the next step towards an industrial application of these oxidoreductases